Adaptive Backstepping Control of Electrical Transmission Drives with Elastic, Unknown Backlash and Coulomb Friction Nonlinearity - Huỳnh Văn Đông; Trần Xuân Kiên; Nguyễn Công Định (ASEAN Journal on Science and Technology for Development, 2010)
In this paper, we present a new scheme to design an adaptive controller for uncertain nonlinear systems with unknown backlash, Coulomb friction nonlinearity. The control design is achieved by introducing a smooth approximate backlash model and certain well defined functions and by using backstepping technique. Itis shown that the proposed controller can guarantee that the system is global asymptotic stable.